Elucidation of morphological and physiological traits contributing to high biomass productivity and consistently high yield in the high-yielding rice variety Kitagenki - Yagioka, Atsushi; Hayashi, Satoshi; Kimiwada, Kenji; Kondo, Motohiko (Frontiers in Plant Science, 2025)
IntroductionA high-yielding rice variety (HYV), Kitagenki, in the Hokkaido region has a high yield potential owing to its large sink capacity, high source ability, and grain-filling ability. However, the detailed mechanisms underlying high biomass productivity, a major component of source ability, and stable high yields remain elusive. Thus, we aimed to elucidate the canopy morphological and physiological traits that improve the biomass productivity of Kitagenki and how they contribute to a stably high yield.MethodsWe conducted field experiments over 8 years using three rice varieties (Nanatsuboshi: standard-yielding variety, Kita-aoba, and Kitagenki: HYV) with three replicates.Results and discussionKitagenki stably produced higher gross hulled grain yield than Kita-aoba by 4.9–14.9% (8.9% on average) because of higher filled-grain percentage. During 0–20 days after the full-heading stage (DAH), Kitagenki revealed a markedly higher crop growth rate by 29.7% than Kita-aoba because of a higher net assimilation rate while maintaining leaf area index. During these stages, Kitagenki showed a better canopy architecture, characterized by substantially higher leaf inclination angles of the upper two leaves and narrower leaf blades, which facilitated better light interception inside the canopy and higher 13C assimilation of the third and whole leaves than in Kita-aoba. At the single-leaf level, Kitagenki showed a higher photosynthetic rate in the third leaf and higher stomatal conductance. Consequently, adequate carbohydrate supply during the early grain-filling stages in Kitagenki enabled faster translocation into the inferior spikelet, resulting in a higher grain-filling ability than that in Kita-aoba. This further contributed to the higher grain yield per cumulative solar radiation during 0–40 DAH in Kitagenki than in Kita-aoba under fluctuating air temperature. These findings indicate that superior canopy architecture, better light interception inside the canopy, and higher carbon assimilation of lower leaves contribute to high biomass productivity during the early grain-filling stage, leading to high grain-filling ability and a stable high yield in Kitagenki compared to Kita-aoba. These results provide key canopy morphological and physiological traits for breeding future HYV that can break the yield ceiling in cold regions.